Efeitos da eletroacupuntura sobre a peritonite polimicrobiana induzida por inoculação intraperitoneal de fezes em camundongos - Brito, Eliana Ferraz de (2010)
Introduction. Acupuncture and electroacupuncture have anti-inflammatory effects as demonstrated in experimental models and some observations in humans, but little is known about their impact on the evolution of infections. There is one observation on effects of acupuncture in the early stages of sepsis induced by cecal ligation and puncture in rats, showing a reduction of bacteria in the first six hours. Objectives. To study the effects of electroacupuncture on the evolution of a polymicrobial peritonitis by intraperitoneal inoculation of feces in mice. Material and Methods. Male Swiss mice, 6-8 weeks old, were anesthetized with ketamine and xylazine and inoculated by intra-peritoneal route with 4μl / g body weight of a suspension of feces diluted to 1:9 (weight / vol in saline). Immediately after, a group received the needles in points E36 and VB-30, bilaterally, remaining without any manipulation, and other group received the needles on the same points with electrical stimulation (2 Hz) for 30 minutes. In one experiment the neutrophils in the peritoneal exudates were counted 24 h after induction of peritonitis and in another experiment the animals were followed up for 14 days when they were euthanized for counting and measurement of intraperitoneal abscesses. Results. Significant increase in the number of neutrophils in the peritoneal cavity and reduction in number and size of intraperitoneal abscesses were observed in the animals receiving electroacupuncture. Conclusion. Electroacupuncture increased the resistance of mice to polymicrobial peritonitis induced by a suspension of feces. This conclusion is supported by the higher exudation of neutrophils in the first 24 hours and the lower number and size of intra-peritoneal abscesses evaluated 14 days after peritonitis induction. A possible explanation for the observed result would be the effect of EA releasing sympathetic mediators and endorphins enhancing the innate immunity by acting on α-adrenergic receptors of peritoneal macrophages and stimulating the activity of natural killer cells